Systemic Dual-Developmental Supervision: An Approach for Psychotherapy Practitioners and Supervisors. (January 2017) - Harris, Shaywanna
Counseling programs utilize supervision to train ethical and effective professionals. Faculty supervisors may incorporate systemic interventions into their supervision of students from mental health, school counseling, and marriage and family therapy tracks, as students may encounter systemic clients in their tenure as therapists. Further, many existing supervision models focus on supervisee development and neglect the developmental considerations of supervisors. The systemic dual-developmental supervision model integrates systemic supervision to address the developmental needs of not only the supervisee but the supervisor as well.